Enhancement of antitumor effects of berberine chloride with a copper(II) complex against human triple negative breast cancer: In vitro studies - Duaa R. Alajroush; Brittney F. Anderson; Janae A. Bruce; Christian I. Lartey; Dazonte A. Mathurin; Sean T. Washington; Tanaya S. Washington; Sidy Diawara; Sakariyau A. Waheed; Kaylin L. Thomas; Stephen J. Beebe; Alvin A. Holder (Results in Chemistry)
In this study, the copper(II) complex [Cu(chromoneTSC)Cl2]•0.5H2O•0.0625C2H5OH (where chromoneTSC = (E)-N-Ethyl-2-((4-oxo-4H-chromen-3-yl)methylene)-hydrazinecarbothioamide) was synthesized and characterized; then used to carry out in vitro studies in combination with berberine chloride (BBC). The ligand and complex were characterized by elemental analysis, FTIR and NMR (1H and 13C) spectroscopy, and conductivity measurements. The cytotoxic effect was analyzed by using the CCK-8 viability assay in cancer MDA-MB-231 VIM RFP and non-cancer MCF-10A cell lines. The IC50 values for the complex and BBC were 21.2 ± 1.6 and 48.3 ± 2.4 μM, respectively at 24 h incubation, while the IC50 value of the combination treatment was 9.3 ± 1.5 in cancer cells. The co-treatment group significantly increased the number of cells in G2 phase, indicating the growth arrest of cancer cells. Moreover, the combination group showed induction of both intrinsic and extrinsic apoptotic pathways. There was also a study on the effect of the combination treatment on receptor-interacting serine/threonine-protein kinase 3 (RIPK3) and mixed lineage kinase domain-like pseudokinase (MLKL) as biomarkers of necroptosis. The results showed activation of necroptosis after treatment with the combination of the copper complex and BBC via the activation of RIPK3–MLKL pathway.